Menganalisis Kegiatan Anak pada Perkembangan Aspek Sosial dan Emosional Usia 5-6 Tahun Kelas B1 TK Darussalam Palembang - Syiran aAlmudzalifah; Attyah Naysah; Allyka Ramadani Azzahra; Rukiyah Rukiyah; Lia Dwi Ayu Pagarwati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Social-emotional development is an important aspect in early childhood development, because it is related to children's ability to interact with others, control emotions, and adapt to their social environment. This ability is very necessary for children to build good relationships with peers and teachers in the school environment. This study aims to determine and describe children's social-emotional development during the learning process in class B1 Darussalam Kindergarten Palembang. This study uses a qualitative descriptive approach with direct observation methods through observation techniques. The subjects in the study consisted of 11 children aged 5-6 years. The results of the observation showed that some children were able to participate in learning in class activities well, such as praying, singing, playing, and following teacher directions. However, one child was found to exhibit behavior in his social-emotional development that was still not optimal, such as lack of focus during learning, biting fingers, pinching friends, liking to stick to one of the researchers and being less involved in group activities. This indicates the need for appropriate guidance and stimulation from teachers to improve the ability to manage emotions, concentration, and social skills.